Value of 3-Dimensional Digital Subtraction Angiography for Detection and Classification of Intracranial Aneurysm Remnants After Clipping. Issue 2 (16th April 2021) - Marbacher, Serge; Halter, Matthias; Vogt, Deborah R; Kienzler, Jenny C; Magyar, Christian T J; Wanderer, Stefan; Anon, Javier; Diepers, Michael; Remonda, Luca; Fandino, Javier
Abstract: BACKGROUND: The current gold standard for evaluation of the surgical result after intracranial aneurysm (IA) clipping is two-dimensional (2D) digital subtraction angiography (DSA). While there is growing evidence that postoperative 3D-DSA is superior to 2D-DSA, there is a lack of data on intraoperative comparison. OBJECTIVE: To compare the diagnostic yield of detection of IA remnants in intra- and postoperative 3D-DSA, categorize the remnants based on 3D-DSA findings, and examine associations between missed 2D-DSA remnants and IA characteristics. METHODS: We evaluated 232 clipped IAs that were examined with intraoperative or postoperative 3D-DSA. Variables analyzed included patient demographics, IA and remnant distinguishing characteristics, and 2D- and 3D-DSA findings. Maximal IA remnant size detected by 3D-DSA was measured using a 3-point scale of 2-mm increments. RESULTS: Although 3D-DSA detected all clipped IA remnants, 2D-DSA missed 30.4% (7 of 23) and 38.9% (14 of 36) clipped IA remnants in intraoperative and postoperative imaging, respectively (95% CI: 30 [ 12, 49] %; P -value .023 and 39 [23, 55] %; P -value = <.001), and more often missed grade 1 (< 2 mm) clipped remnants (odds ratio [95% CI]: 4.3 [1.6, 12.7], P -value .005). CONCLUSION: Compared with 2D-DSA, 3D-DSA achieves a better diagnostic yield in the evaluation of clipped IA. Our proposed method to grade 3D-DSA remnants proved to be simple and practical. Especially small IA remnants have a high risk to be missed in 2D-DSA. We advocate routine use of either intraoperative or postoperative 3D-DSA as a baseline for lifelong follow-up of clipped IA.